2020
DOI: 10.3390/w12113136
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Kalman Filter for a Geostatistical Bivariate Spatiotemporal Estimation of Hydraulic Conductivity in Aquifers

Abstract: The estimation of the hydraulic parameters of an aquifer such as the hydraulic conductivity is somehow complicated due to its heterogeneity, on the other hand field and laboratory tests are both time consuming and costly. The use of geostatistical-based techniques for data assimilation could represent an alternative tool that allows the use of space-time aquifer behaviour to characterize hydraulic conductivity heterogeneity. In this paper, a spatiotemporal bivariate methodology was implemented combining histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…Under the practical point of view, the model chosen for the random function is bound to be the space continuity of the sampled data set. The above representation has been applied to flow measurement [ 23 , 24 ], particularly to detect the third component of Table 2 . We can say that the approach adopted in this paper is correct, given the fact that the velocities represented in Figure 10 (+symbols) fall within the range of uncertainty designated in the paper.…”
Section: Expanded Metrics For Comparison: Geostatistics and Sobol-bas...mentioning
confidence: 99%
“…Under the practical point of view, the model chosen for the random function is bound to be the space continuity of the sampled data set. The above representation has been applied to flow measurement [ 23 , 24 ], particularly to detect the third component of Table 2 . We can say that the approach adopted in this paper is correct, given the fact that the velocities represented in Figure 10 (+symbols) fall within the range of uncertainty designated in the paper.…”
Section: Expanded Metrics For Comparison: Geostatistics and Sobol-bas...mentioning
confidence: 99%
“…However, simulated drawdowns and the Cooper-Jacob solution deviate significantly from the measurements for times greater than 500 min. For comparison purposes, in Table 3 are also presented the values for 𝑇 and 𝑆 reported in [27] obtained with traditional methods (Theis and Cooper-Jacob procedures) For comparison purposes, in Table 3 are also presented the values for T and S reported in [27] obtained with traditional methods (Theis and Cooper-Jacob procedures) and using an adaptative pumping test analysis based on the Kalman filter (the Şen procedure); the results of using the software AquiferWin32 version 4.00 [16] are also included. In Table 3, it can be observed that the values reported in [27] for T and S differ considerably from those found with the procedure proposed in this paper.…”
Section: The Aquifer Test "Oude Korendijk"mentioning
confidence: 99%
“…For comparison purposes, in Table 3 are also presented the values for 𝑇 and 𝑆 reported in [27] obtained with traditional methods (Theis and Cooper-Jacob procedures) For comparison purposes, in Table 3 are also presented the values for T and S reported in [27] obtained with traditional methods (Theis and Cooper-Jacob procedures) and using an adaptative pumping test analysis based on the Kalman filter (the Şen procedure); the results of using the software AquiferWin32 version 4.00 [16] are also included. In Table 3, it can be observed that the values reported in [27] for T and S differ considerably from those found with the procedure proposed in this paper. When the former parameters are used to obtain drawdowns with the Cooper-Jacob solution, significant differences are obtained with respect to the measurements, especially for larger times.…”
Section: The Aquifer Test "Oude Korendijk"mentioning
confidence: 99%
See 1 more Smart Citation
“…Protection the groundwater quality is important, the major approach to the protection of groundwater is the monitoring and estimate of the chemical, physical and biological substances of it (Jang et al, 2013). Monitoring groundwater and collecting data from the process of monitoring provides an understanding of the situation of groundwater (Júnez-Ferreira & Herrera, 2013;Mogheir et al, 2006). An excellent monitoring scheme would suggest both accurate and sufficient groundwater property data as well as cost-effectively fair data (Baalousha, 2010).…”
Section: Introductionmentioning
confidence: 99%